Mengenal Human Metha Pneumo Virus (HMPV) yang merebak di beberapa Negara - Kadriyan, Hamsu (Lombok Medical Journal, 2025)
Abstract Human Meta Pneumo Virus (HMPV) is a single strain virus identifies as a cause of upper airway infection. Recently, several new cases reported in some countries, including Indonesia. After the virus infected the epithelial cell, it will replicated exponentially and spreading to adjacent cells. As a result, it will break the tissue and lead to inflammation. In patient with immunocompromised, HMPV infection will continued to pneumonia and other serious complication. Therefore, it is necessary to inform this virus characteristics to the health care professionals to allow them can tackle the disease accurately. Finally, it could limiting the potency of the occurrence of epidemic in population.